Growth and Development of Agricultural Education, Research, and Libraries in India - Singh, K.P. (DESIDOC Journal of Library & Information Technology, 2011)
Agriculture in India, since ancient times, is the most crucial sector for ensuring food and nutritional security,sustainable development and for the alleviation of poverty. It is the key sector in India for generating employmentopportunities for the vast majority of the population particularly in rural areas. The paper aims to explore themany facets related to agricultural education, research, training, and libraries in India in order to provide ahistorical account on these aspects. The paper discusses in detail the various committees and commissions andtheir salient recommendations leading to the expansive growth and development of agricultural education, research,and libraries in India. Further, the paper also highlights the critical role of the Indian Council of AgriculturalResearch in the growth and development of agricultural education, research, extension, and libraries. http://dx.doi.org/10.14429/djlit.32.2.1400